Separation axioms for partially ordered convergence spaces - Reino Vainio (International Journal of Mathematics and Mathematical Sciences)
In partially ordered convergence spaces, separation axioms are introduced and then related to the concept of complete separatedness due to Nachbin as well as to connectedness concepts. A method to generate new separation axioms is studied.